The “Evangelical International” and the split of Ancient and Accepted Scottish Rite in Italy in 1908 - Novarino, Marco (2022)
In 1908 there was a severe schism in the Ancient and Accepted Scottish Rite of Italy and, consequently, in the Grande Oriente d’Italia. The main actors were protestant pastors. The “protestant” conspiracy didn’t cause the split, but the international evangelmassoniche relationships of the secessionists helped the new masonic organism survive thanks to their prestigious international awards. The good political qualities and the hard work of pastor Saverio Fera and his close associates made this possible, even if the churches, to which they belonged, had nothing to do with it.